Galapagos farmers: risk and the coexistential rift - Stimson, JR (2023)
Galapagos farmers are generally invisible in global discourses and remain understudied from an anthropological perspective. Drawing on a year of ethnographic fieldwork during the 2020-2021 global pandemic, this thesis focuses on their main worries and livelihood challenges. The liminal period created during the Covid-19 pandemic brought back many aspects of life prior to the arrival of the archipelago’s tourism industry and led farmers to yearn for a nostalgic, utopian past when they coexisted more harmoniously with each other and the environment. Unfortunately, many elements of that idealized life are currently unattainable due to compounding risks, including pests, climate change, and Covid-19. The everyday threats to farmers’ livelihoods have led to market dependence, indebtedness, alienation, and cumulative anxiety. I explore each risk ethnographically, whilst also showing the ways in which they are part of a causal framework that alters farmers’ values and behaviours. This thesis formulates the coexistential rift concept to explain how both the materiality of risks and their perception accelerate a treadmill syndrome where farmers must focus on making money to lessen their insecurity. This vicious cycle is reinforced by the slow violence of political abandonment, economic inequality, fortress conservation, legal and bureaucratic obstacles, and predominant metanarratives that blame and exclude the archipelago’s inhabitants. Both Galapagueño society and the environment would benefit from addressing the agricultural sector’s long-standing problems. Finally, this thesis points to how human and political ecological studies can better conceptualize and incorporate risks into their analysis and causal frameworks to elucidate their impact on everyday life.